RISK FACTORS OF MEDICAL DEVICE-RELATED PRESSURE INJURY IN CHILDREN IN THE INTENSIVE UNIT: A SYSTEMATIC REVIEW - Aina Aprilma Ray; Nani Nurhaeni; Imami Nur Rachmawati (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Around 30% of hospital-acquired pressure injuries are caused by the use of medical devices. Children who are treated in intensive care units are at risk for medical device-related pressure injuries (MDRPI). This incident needs to be prevented considering the impact it has, namely prolonging hospitalization, increasing pain, increasing treatment costs, and requiring further care after discharge from the hospital. This review aims to identify risk factors that contribute to MDRPI in children who are in intensive care. A systematic review was carried out through a search strategy on an electronic database. A total of eight articles were selected and quality was assessed using the JBI critical appraisal guidelines. The face is the most frequently affected location for pressure injuries (54.5%), followed by the occiput (18.2%). Factors that contribute to MDRPI in children treated in the intensive care unit are the length of stay in the hospital, age of the respondent, knowledge of the nurse, attitude of the nurse, work experience of the nurse in the intensive care unit, leakage of the NIV mask, duration of device use, and gestational age. It is expected that nurses can carry out accurate risk assessments and apply appropriate interventions to prevent MDRPI events.